DIMENSI SPIRITUAL DALAM SENI LUKIS ABSTRAK KONTEMPORER INDONESIA: SEJARAH DAN WACANA - gozali, amir (Institut Seni Indoensia Surakarta, 2019)
AbstractAbstract art through its abstraction mode is an attempt to explore the essence and existence of humanityin the dimension of spirituality. Abstraction is able to present a deeper meaningful space because of theopen dialogue between artists - works - spiritual observers. This research was conducted to explore andexplore the transcendental and spirituality dimensions especially in contemporary Indonesian abstractpainting as part of the expression and reflection of the search for the essence of the artist. In addition,historical aspects and discourse dynamics will also be analyzed in order to obtain a comprehensiveunderstanding in understanding the development of abstract art in Indonesia. This study uses qualitativemethods by optimizing studies on written sources and literature relating to the study of contemporaryIndonesian abstract painting by further analyzing the historical aspects and dynamics of discourse. Datawere analyzed using content analysis method. This study is expected to be a reference material for learningabstract art, artists, and art lovers.Keywords: spiritual, abstract painting, contemporary art, Indonesia